A taxonomic review of the genus Hemiphractus (Anura: Hemiphractidae) in Panama: Description of Two New Species, Resurrection of Hemiphractus panamensis (Stejneger, 1917), and Discussion of Hemiphractus fasciatus Peters, 1862 - Hill, Robert L.; Martin, Kathryn G.; Stanley, Edward; Mendelson, Joseph R. Iii (Zootaxa, 2018)
We reviewed the taxonomic status of populations of frogs in the genus Hemiphractus in Panama, which have all been referred to Hemiphractus fasciatus Peters, 1862 for over 40 years. Although relatively few specimens have been collected, mostly juveniles, it is clear that these frogs inhabit three separate upland regions of the country: The Cordillera de Talamanca in western Panama, the Chagres Highlands and Cordillera de San Blas in central Panama, and the Serranía de Pirre in the far eastern portion of the country. In accordance with previously published molecular data, we identified distinctive features of the skulls of frogs representing these three allopatric populations and herein revalidate H. panamensis (Stejneger, 1917), describe the new species Hemiphractus elioti sp. nov. from the Cordillera de Talamanca, and the new species Hemiphractus kaylockae sp. nov. from the Serranía de Pirre. We also propose that the taxon H. fasciatus is a South American species not occurring in Panama.